2021
DOI: 10.2147/ijgm.s303350
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Serum Calcitonin Gene-Related Peptide and Apolipoprotein E in Migraine: A Preliminary Study

Abstract: Background A reliable, migraine-specific biomarker has not been identified so far. Calcitonin Gene-Related Peptide (CGRP) and Apolipoprotein E (ApoE) might serve as migraine biomarkers due to their roles in migraine pathophysiology. However, their diagnostic usefulness has not been explored yet. Present study explored the diagnostic accuracy of CGRP and ApoE in migraine. Methods A cross-sectional, case–control study was conducted from November 2019 to April 2020 at Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Interestingly, a positive correlation between serum CGRP levels and pain intensity was also reported [ 41 ]. It must, however, be noted that other studies did not report any changes in CGRP levels among EM and CM patients [ 42 , 43 , 44 , 45 , 46 ].…”
Section: The Potential Circulating Biomarkers Described In Migraine P...mentioning
confidence: 80%
See 1 more Smart Citation
“…Interestingly, a positive correlation between serum CGRP levels and pain intensity was also reported [ 41 ]. It must, however, be noted that other studies did not report any changes in CGRP levels among EM and CM patients [ 42 , 43 , 44 , 45 , 46 ].…”
Section: The Potential Circulating Biomarkers Described In Migraine P...mentioning
confidence: 80%
“…Some studies clearly show an increase in plasma/saliva CGRP levels during the attack compared with the interictal period in EM patients [ 34 , 40 , 48 , 49 , 50 ]. By contrast, other studies reported no difference in CGRP levels in jugular venous blood between the ictal and interictal periods in EM subjects [ 45 , 51 ]. Similarly, Cady and colleagues showed no difference in the CGRP saliva levels of CM patients during a migraine attack compared with EM patients, suggesting that the threshold for central activation from peripheral input is possibly lower in CM than in EM [ 52 ].…”
Section: The Potential Circulating Biomarkers Described In Migraine P...mentioning
confidence: 83%
“…In Saudi Arabia, the prevalence of migraines in females is around 26.9% and is considered higher than the global average [ 6 , 7 ]. In addition, recent studies in this population revealed that high oestrogen levels could be involved in mediating the non-menstrual-related migraine among young Saudi females [ 8 ], and serum ApoE was reported as an excellent diagnostic marker for the same subjects with migraine in ictal or interictal phase [ 9 ]. However, genetic studies are deficient concerning migraines in this population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can also be classified into a chronic and episodic migraine. Hemiplegic migraine is another type of MA and is a severe and rare condition that affects one side of the body and causes temporary numbness [ 9 ]. It once was believed that migraine is a vascular disease; however, many recent types of research confirmed the involvement of multiple mechanisms related to the brain structures and processes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can also be classi ed into chronic and episodic migraine. Hemiplegic migraine is another type of MA and is a severe and rare condition that affects one side of the body and causes temporary numbness [7]. The old theory on the cause of migraine considered it as a vascular disease; However, many recent researches con rmed the involvement of multiple mechanisms related to the brain structures and processes [8].…”
Section: Introductionmentioning
confidence: 99%